(3MGTjI Ydi MGTjI GdJaJGRGfjs - (3eLghds
(3ChdgG (B:s
(3ChdgG(B: (3Edi GdTjA jDNP hGdeQGO ZGjI hVY eJYdb HeG SHb efg bhdg(B: (3CHjJ hCTQJ, hGdGQJMGd gh GdEJjGf HGdTYQ hZjQg ef ZjQ QhjIs
(3BNQgG (B:s
(3BNQgG(B: (3gPg GdcaQGJ GdeaQhV CfgG (B.. (3eJYOOI HMSH faS GdCeQ (B.. (3Cbhd(B: (3HCajO ef GddRhe (B.. (3CeG GdaQb Hjf RjO hSGFQ GdLRFjGJs
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdadSaI hGdefWbs